2014
DOI: 10.3233/jad-140417
|View full text |Cite
|
Sign up to set email alerts
|

Motor Effects of Radio Electric Asymmetric Conveyer in Alzheimer's Disease: Results from a Cross-Over Trial

Abstract: We conducted a randomized, cross-over trial to investigate the feasibility, safety, and motor effects of brain stimulation with radio electric asymmetric conveyer (REAC) technique in patients with Alzheimer's disease (AD). Neuropostural optimization (NPO) and sham protocol were administered to 60 patients from the nursing home and day care units of the Alzheimer Center Reina Sofía Foundation. The mean age was 84.1 (SD 7.9) years and 86.7% of the subjects were female. Motor measures were collected at baseline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 16 publications
2
30
0
2
Order By: Relevance
“…In particular, CP animals showed significant signs of restoration of the normal thalamocortical neurophysiology after sessions of REAC applications, that is, at the best of our knowledge, the REAC application configures as the first non-invasive intervention able to modify the pathophysiology of the CP in a very short time range. Changes of CP spiking and LFP patterns appear, on the other hand, coherent with clinical findings on chronic pain 6 9 . More in general, REAC applications promote the synchronization of the neuronal activity, a clear sign of an augmented communication among neurons possibly able to promote the information integration necessary to boost the normal information processing of the system.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In particular, CP animals showed significant signs of restoration of the normal thalamocortical neurophysiology after sessions of REAC applications, that is, at the best of our knowledge, the REAC application configures as the first non-invasive intervention able to modify the pathophysiology of the CP in a very short time range. Changes of CP spiking and LFP patterns appear, on the other hand, coherent with clinical findings on chronic pain 6 9 . More in general, REAC applications promote the synchronization of the neuronal activity, a clear sign of an augmented communication among neurons possibly able to promote the information integration necessary to boost the normal information processing of the system.…”
Section: Discussionsupporting
confidence: 78%
“…The REAC technology (acronym for Radio Electric Asymmetric Conveyor) is a technology based on low intensity (2 mW at the emitter) microwave emission (2.4 or 5.8 GHz) able to interact with biological tissues by inducing radiofrequency generated microcurrents conveyed in an asymmetric manner 1 2 . It shows remarkable biological effects at many scales from gene modulations up to functional global remodeling of districts or in human subjects 3 4 5 6 7 8 9 10 . Those relevant to the central nervous system include, for instance, significant effects at the cellular stem-cell 3 4 5 and the general levels in neurological and neurodegenerative disorders disease 6 or in the treatment of generalized and social anxiety disorders 7 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When used according to a specific protocol (neuro-postural optimization –NPO- 250 milliseconds), it induces long-lasting changes in brain activation 7 and improves balance in patients suffering from various neurological diseases 8 , as observed by functional magnetic resonance imaging (fMRI) 7 9 10 . The impact of REAC-NPO treatment has also been explored in AD patients in a pilot randomized controlled trial 11 and in a randomized cross-over trial 12 designed to investigate the feasibility, safety, and short-term motor effects in patients with advanced AD, who also experience motor deterioration. Both these studies provided promising, albeit preliminary, results.…”
mentioning
confidence: 99%
“…Until now, REAC technology has been used in clinical studies on several psychiatric and neurological disorders with encouraging results in the absence of side effects ( 6 – 15 ). Studies have also been conducted in AD patients with promising results ( 16 18 ). Moreover, studies at the cellular level have shown that REAC technology, with the appropriate protocols, is able to induce neuronal differentiation both in murine embryonic cells and in human adult differentiated cells ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%